EVALUASI PENEMPATAN PEGAWAI NEGERI SIPIL DALAM JABATAN STRUKTURAL DI KABUPATEN KENDAL TAHUN 2013 - Nisria Fairuz Husna; Muhammad Adnan; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2015)
Structural local government official have important and strategic role in order to guarantee the success of government’s job, development and service to the people, therefore implementation of civil servant appointment and placement in structural position must comply with regulations to ensure quality, objectivity and transparency of the policy. In Kendal, there are some civil servants who placed in structural position which are considered less appropriate between their structural position and formal educational backgrounds.This research aims to find out and evaluate placement of civil servant in structural position in Kendal regency based on Regional Regulation (Perda) of Kendal No. 2 of 2012. The method of this research is qualitative descriptive using interviews and document study as data collection techniques.The results of this research described that civil servant placement process in structural position in Kendal is not fully appropriate with Regional Regulation (Perda) of Kendal No. 2 of 2012. Civil servant placement in structural position also describe that the process lack of transparent and not implemented yet merit system purely. Furthermore there are some civil servants who placed in structural position that is not appropriate with educational term which is prioritize in competency standards of structural position, due to the lack of civil servants who have an educational background in specific sector. Keywords: Civil servant, structural position, placement, structural local government official